A Behavioristic Theory - Vina Naila Muna (Universitas HKBP Nommensen, 2021)
Learning is a process of changing behavior from an experience. Behavioristic learning theory is a learning theory that prioritizes changes in student behavior as a result of stimuli and responses. The characters in behavioristic theory are Ivan P. Pavlov, Edward Lee Thorndike, BF Skinner, and John Broadus Watson. The use of behavioristic theory in the learning process requires humans to be more likely to be responsive to the stimuli given and then produce good behavior. Therefore, there are general principles of behavioristic theory, namely learning is a change in behavior, learning is a stimulus and response, and reinforcement, which is anything that